SEKURITISASI WACANA KHILAFAH DI INDONESIA - Prihandono Wibowo (The Indonesian Islamic Studies and International Relations Association (Insiera), 2020)
Caliphate restoration is a religious expression that has developed widely in Indonesia since the reformation era in 1998. Historical romanticism, the study of Islamic political jurisprudence, and Islamic eschatology are the basis for the development of religious expressions regarding the restoration of the Caliphate in Indonesia. Since the reformation era, various Islamic groups have idealized the restoration of the Caliphate with a variety of methods. The discourse regarding the Caliphate idea developed widely in society. However, in contemporary Indonesian politics, the Caliphate idea is identified by the State as a dangerous discourse for State sovereignty. Caliphate's discourse is identified with the trend of radicalism and terrorism. Religious groups that have longing expressions of the existence of the Caliphate are identified as